A carbonized path material for detection, preparation method and application thereof
By preparing the mixture of ABS, PVC and epoxy fiberglass laminate at high temperature, the problems of instability and low success rate of carbonization channels in the prior art are solved, and the stability and accuracy of carbonization path materials are achieved. , suitable for large-scale mass production and environmental protection requirements.
Patent Information
- Application Number
- CN202210918773.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-02
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-08-02
AI Technical Summary
In the prior art, the carbonization path material preparation method has the unstable carbonization channel formed, the success rate is low, and requires high pressure assistance, which is not safe enough, and will produce toxic substances, which is not energy-saving and environmentally friendly enough.
A mixture of ABS, PVC and epoxy fiberglass laminates is made into a carbonized path material for detection. It is heated to a high temperature of 700-1000°C, and then the carbonized path material is obtained by filtration and extraction, and tetrachlorine is passed through Carbon extraction and recrystallization improve purity and stability.
It improves the stability and success rate of carbonized path materials, reduces the use of high pressure, reduces the production of toxic substances, and achieves large-scale mass production of materials and the accuracy of test results.
Smart Images

Figure CN115343582B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of distribution line fault arc detection, and in particular to a carbonized path material for detection, a preparation method and application thereof. Background Art
[0002] Due to historical reasons, the fire resistance level of cultural relics buildings is much lower than that of general industrial and civil buildings, and there are phenomena such as mismatch between load and distribution system, obsolete electrical facilities, aging lines, and irregular electricity use. At the same time, the power supply and distribution system of cultural relics buildings has large voltage fluctuations, poor line consistency, complex load types, large distributed capacitance, and serious interference signals. Due to these problems, fault arc interference is easily generated in the power grid. When a fault arc occurs, it will generate instantaneous high voltage and discharge to the surrounding air. In the process, it will generate very high heat, which is very easy to ignite the surrounding combustibles. Most of the electrical fires that have occurred in recent years are also related to fault arcs.
[0003] The detection of fault arcs is highly valued at home and abroad. UL1699 standard for fault arc detectors was issued abroad a long time ago. In 2014, China also issued GB 14287.4-2014 "Fault Arc Detector for Electrical Fire Monitoring System" standard. The preparation of carbonization path in the standard is produced by high-voltage discharge of two wires that are very close but not in contact. At present, the specific practice of carbonization path materials in China is summarized as follows: 15kV±10% high voltage is applied to the cable sample, 10 seconds ON and 10 seconds OFF are repeated, and the transformer provides 30mA current through the insulation part of the cable specimen to create a carbonization conduction path. However, this method has the problems of unstable carbonization channel, low success rate, high voltage assistance, unsafe, and will produce a large amount of dioxins, hydrogen chloride, benzene rings and other toxic substances, which is not energy-saving and environmentally friendly.
[0004] Therefore, there is an urgent need in the current market for a test material that has a high yield, a uniform carbonization path, can be industrially mass-produced, and has accurate test results for detecting the qualification degree of fault arc devices. Summary of the invention
[0005] Purpose of the invention:
[0006] The purpose of the present invention is to provide a method for preparing a carbonization path material for detection and its application, in order to address a series of problems in the prior art, such as the unstable carbonization channel formed, low success rate, need for high pressure assistance, lack of safety, generation of a large amount of toxic substances such as dioxins, hydrogen chloride, benzene rings, etc., lack of energy conservation and environmental protection, etc., which will contribute to the large-scale mass production of carbonization path materials.
[0007] The technical solution of the present invention:
[0008] A carbonized path material for detection is made by carbonizing a mixture of ABS, PVC and epoxy glass fiber cloth laminate; the epoxy glass fiber cloth laminate model is 3240, which is made of electrical glass cloth impregnated with epoxy resin, dried and hot pressed; the addition mass ratio of the ABS, PVC and epoxy glass fiber cloth laminate can be selected from a certain ratio of 5 to 3:1 to 2:1 to 2.
[0009] In other aspects, the present invention also provides a method for preparing a carbonized path material for detection, comprising:
[0010] ABS, PVC and epoxy glass fiber cloth laminate are mixed, heated to carbonization and combustion, filtered after combustion is completed, and the combustion products are extracted; the combustion products are extracted and recrystallized to obtain carbonization path materials.
[0011] In some embodiments, the epoxy glass cloth laminate is model 3240, which is made of electrical glass cloth impregnated with epoxy resin, dried and hot-pressed.
[0012] In some embodiments, the addition mass ratio of the ABS, PVC and epoxy glass fiber cloth laminate can be selected from a certain ratio of 5-1:5 to 1:5-1; wherein the content of ABS is preferably higher than that of PVC and epoxy glass fiber cloth laminate, and preferably, the addition mass ratio of the ABS, PVC and epoxy glass fiber cloth laminate is 5-3:1-2:1-2.
[0013] In some embodiments, the heating to carbonization and combustion is to place the ABS, PVC and epoxy glass fiber cloth laminate mixture in a muffle furnace or other high-temperature closed container for heating, the heating temperature is 700-1000°C, the heating time is 0.5-2h, and the mixture is carbonized to the carbonization path material; the carbonization degree of the material under the carbonization conditions of different temperatures and different times is different, which affects the final structure, and at the same time affects its accuracy and stability as a fault arc path.
[0014] In some embodiments, the extraction is performed using carbon tetrachloride, the purpose of which is to extract the powdered carbonized material from other impurities to ensure the purity and stability of the carbonized channel.
[0015] In other aspects, the present invention also provides a fault arc detector, comprising the above-mentioned carbonized path material for detection, wherein the carbonized path material for detection is encapsulated with an insulating material, and copper conductors are respectively provided on the inner sides of the upper and lower ends of the insulating material, and the copper conductors are in contact with the carbonized path material; wherein the insulating material is not limited in form, and may be an insulating capsule, an insulating bag or an insulating tape, etc., and the insulating material is not limited in material, and is connected to the live wire and the neutral wire of a 220V AC power supply through the upper and lower copper conductors respectively through external copper wires for use.
[0016] In some embodiments, the distance between the copper conductors at the upper and lower ends of the carbonization path product for detection in the package is 2 to 5 mm. Within this range, the normal use of the fault arc material can be effectively guaranteed. When the distance is lower than 2 mm or higher than 5 mm, the copper conductors are too close or too far apart, the carbonization channel is unstable, and the fault arc material cannot function normally.
[0017] In some embodiments, the present invention also provides the use of the above-mentioned carbonized path material for detection or the above-mentioned arc fault detector in detecting arc fault products. Specifically, the carbonized path product for detection can be connected in series with a commercially available arc fault detection product, a 220V power supply, a switch, an oscilloscope, and a load in the same closed circuit, and the qualification of the product can be determined by whether the commercially available arc fault detection product alarms normally; if the alarm is normal, it means that the commercially available arc fault detection product is qualified, and if the alarm cannot be normal, it means that the commercially available arc fault detection product has quality problems and cannot be shipped.
[0018] Beneficial effects:
[0019] The present invention provides a preparation method of a carbonization path material for detection and its application, which can be applied to the simulation of carbonization paths in laboratories, and can also be applied to product factory inspection of arc fault detection product manufacturers, thereby reducing the time cost of artificially carbonizing the external insulating material of the conductor through high voltage, improving the efficiency of material preparation and the accuracy of testing, and being conducive to the large-scale mass production of carbonization path materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The present invention is further described below with reference to the accompanying drawings:
[0021] Figure 1 This is a schematic diagram of the structure of the carbonized path capsule for detection prepared by the present invention; wherein 1 is the carbonized path material, 2 is the insulating material, 3 is the copper conductor, 4 is the external copper wire, and 5 is the copper wire outside the capsule.
[0022] Figure 2 The carbonized path material-1 prepared in Example 1 was placed in a closed circuit to test the waveform displayed on the oscilloscope of a commercially available fault arc detection product.
[0023] Figure 3 The carbonized path material-4 prepared in Example 4 was placed in a closed circuit to test the waveform displayed on the oscilloscope of a commercially available fault arc detection product.
[0024] Figure 4 The carbonized path material-7 prepared in Example 7 was placed in a closed circuit to test the waveform displayed on the oscilloscope of a commercially available fault arc detection product. DETAILED DESCRIPTION
[0025] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0026] Unless otherwise specified, the raw materials used in the following embodiments of the present invention are all commercially available products. The commercially available fault arc detection products described in the embodiments are purchased from Liaoning Lixian Fire Engineering Co., Ltd. and are qualified products. Unless otherwise specified in the embodiments, the epoxy glass fiber cloth laminate model used is 3240, which was purchased from Zhejiang Haodesheng Insulation Materials Co., Ltd.
[0027] PVC particle size used in the example: diameter x length = 0.5 mm 2 ×5mm±0.5mm, particle mass 10g±1g; ABS particle size used: length×width×height=(5mm×4mm×3mm)±0.2mm, particle mass 10g±1g; epoxy glass fiber cloth laminate size used: length×width×height=(6mm×6mm×1.6mm)±0.2mm, sheet mass 10g±1g.
[0028] Examples 1 to 9
[0029] Carbonized material extraction: In a tubular furnace, the three materials of ABS, PVC and epoxy glass fiber cloth laminate were heated at 700°C by a heating plate until they burned. After heating for 1 hour, the heating was stopped. After the combustion and scorching were completely finished, the smoke in the container was filtered to obtain the combustion products. The mass ratios of the three materials of ABS, PVC and epoxy glass fiber cloth laminate are as described in Table 1.
[0030] Extraction and purification: The combustion product obtained above is extracted with carbon tetrachloride to extract the powdery substance therein.
[0031] Recrystallization: The extracted material is recrystallized to obtain carbonization path materials-1 to 9.
[0032] Table 1 Mass ratio of ABS, PVC and epoxy glass fiber cloth laminates in Example
[0033]
[0034] Comparative Examples 1 to 6
[0035] Carbonized material extraction: In a tubular furnace, one or two of the three materials of ABS, PVC and epoxy glass fiber cloth laminate are heated at 700°C by a heating plate until they burn. After heating for 1 hour, the heating is stopped. After the combustion and scorching are completely finished, the smoke in the container is filtered to obtain the combustion product; the mass ratios of the three materials of ABS, PVC and epoxy glass fiber cloth laminate are shown in Table 2.
[0036] Extraction and purification: The combustion product obtained above is extracted with carbon tetrachloride to extract the powdery substance therein.
[0037] Recrystallization: The extracted material is recrystallized to obtain carbonization path materials -1'~6'.
[0038] Table 2 Comparative Example ABS, PVC and epoxy glass fiber cloth laminated board three added mass ratio data table
[0039]
[0040] Table 3 Data table of carbonization path materials prepared from ABS, PVC and different types of epoxy glass fiber cloth laminates at a mass ratio of 4:1:2
[0041]
[0042] Embodiments 10 to 13
[0043] Carbonized material extraction: In a tubular furnace, the three materials of ABS, PVC and epoxy glass fiber cloth laminate are heated by a heating plate until they burn. After heating for 1 hour, the heating is stopped. When the combustion and burning are completely finished, the smoke in the container is filtered to obtain the combustion product; the mass ratio of ABS, PVC and epoxy glass fiber cloth laminate is 4:1:2. The heating temperature values are shown in Table 4.
[0044] Extraction and purification: The combustion product obtained above is extracted with carbon tetrachloride to extract the powdery substance therein.
[0045] Recrystallization: The extracted material is recrystallized to obtain carbonization path materials -10~13.
[0046] Table 4 Heating temperature data table of Examples 10 to 13
[0047] Example Heating temperature(℃) Material Example 10 500 Carbonization Path Materials-10 Embodiment 11 700 Carbonization Path Materials-11 Example 12 900 Carbonization Path Materials-12 Example 13 1000 Carbonization Path Materials-13
[0048] The above-mentioned carbonized path materials-1~13 and carbonized path materials-1'~8' are encapsulated in insulating capsules, and copper conductors are inserted into the upper and lower ends of the capsules. The copper conductors are in contact with the carbonized path materials. The distance between the conductors on both sides in the capsule is 2mm to avoid contact between the conductors. The copper conductors at both ends are connected to the live wire and the neutral wire of the 220V AC power supply through external copper wires, and are connected in series with commercially available fault arc detection products, 220V power supply, switches, oscilloscopes, and different loads in the same closed circuit. Through the action of strong current, the capsule forms a carbonized conduction path and opens the path. Repeat the test 100 times and calculate the alarm accuracy. The alarm accuracy reflects whether the commercially available fault arc detection products are qualified.
[0049] Table 4 Carbonization path material test results data table
[0050]
[0051]
[0052] Figure 2 , Figure 3 , Figure 4 The oscilloscope display images of the test experiments of Examples 1, 4, and 7 in Table 4 are shown respectively. The waveforms at the bottom of the three images are all enlarged images of the squares of the waveforms at the top. It can be clearly seen that Figures 1 to 3 The waveforms in the figure are not standard sine waves. There are horizontal lines of varying degrees at the extreme points of each waveform, indicating the presence of a fault arc in the circuit. The horizontal lines suddenly rise or fall behind them, and there is instantaneous energy release in the process, which can indicate that there are safety issues in the circuit.
[0053] And from the above experiments and examples, it can be found that the carbonized path material obtained by heating and compounding the three materials of ABS, PVC and epoxy glass fiber cloth laminate can effectively replace the conventional preparation method of existing domestic carbonized path materials, and conduct quality inspection on the fault arc detection products produced and shipped. When the carbonized path material capsule is connected in series with the commercially available fault arc detection product, 220V power supply, switch, oscilloscope, and different loads in the same closed circuit, the passage is opened, and the product qualification is judged by whether the commercially available fault arc detection product can alarm normally. It can reduce the time cost of artificially carbonizing the insulating material outside the conductor through high voltage, improve the efficiency of material preparation, and is conducive to the large-scale mass production of carbonized path materials.
[0054] It can be seen from Table 4 that the ratio of ABS, PVC and epoxy glass fiber cloth laminate has a great influence on the detection results of carbonization path materials. When only one or two materials are carbonized, the alarm results vary greatly, with low accuracy and poor stability, and cannot be used as fault arcs. When ABS, PVC and epoxy glass fiber cloth laminate are mixed, the detection accuracy can be improved, especially when the carbonization temperature is between 700 and 1000°C, the alarm accuracy can reach 99% to 100%, and when the carbonization temperature is between 700 and 900°C, the alarm accuracy can reach 100%.
[0055] The above experimental results show that this method can simplify the preparation process of carbonized path materials for distribution lines, and greatly increase the yield to more than 85%, thereby improving the preparation efficiency of carbonized path materials. In addition, the carbonized path materials prepared by this method can be fully applied to distribution line fault arc detection tests with an accuracy of 99-100%.
[0056] The present invention can also have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.
Claims
1. A carbonized path material for detection, characterized in that: The carbonization path material is prepared by carbonizing a mixture of ABS, PVC and epoxy glass fiber cloth laminates, and the carbonization path material is prepared by the following method, including mixing ABS, PVC and epoxy glass fiber cloth laminates, heating them to carbonization and combustion, filtering after the combustion is completed, and extracting the combustion products; extracting and recrystallizing the combustion products to obtain the carbonization path material.
2. The carbonized path material for detection according to claim 1, characterized in that: The epoxy glass fiber cloth laminate model is 3240.
3. The carbonized path material for detection according to claim 1, characterized in that: The added mass ratio of the ABS, PVC and epoxy glass fiber cloth laminate is 5~3:1~2:1~2.
4. The carbonized path material for detection according to claim 1, characterized in that: The heating to carbonization combustion has a heating temperature of 700-1000° C. and a heating time of 0.5-2 h.
5. The carbonized path material for detection according to claim 1, characterized in that: The extraction is performed using carbon tetrachloride.
6. An arc fault detector, characterized in that: It comprises the carbonized path material for detection as described in any one of claims 1 to 5, wherein the carbonized path material for detection is encapsulated with an insulating material, and copper conductors are respectively provided on the inner sides of the upper and lower ends of the insulating material, the copper conductors are in contact with the carbonized path material, and the copper conductors are connected to external wires through external copper wires.
7. The arc fault detector according to claim 6, characterized in that: The distance between the copper conductors is 2-5 mm.
Citation Information
Patent Citations
PPS (polyphenylene sulfide) engineering plastic with high CTI (comparative tracking index) performance and preparation method of PPS engineering plastic
CN106280460A
Preparation method of composite filler for improving impact resistance of plastic
CN109265746A